(S)-[18F]THK5117 brain uptake is associated with Aβ plaques and MAO-B enzyme in a mouse model of Alzheimer's disease. (15th September 2021) - Alzghool, Obada M.; Rokka, Johanna; López-Picón, Francisco R.; Snellman, Anniina; Helin, Jatta S.; Okamura, Nobuyuki; Solin, Olof; Rinne, Juha O.; Haaparanta-Solin, Merja
Abstract: The mouse model of beta-amyloid (Aβ) deposition, APP/PS1-21, exhibits high brain uptake of the tau-tracer ( S )-[ 18 F]THK5117, although no neurofibrillary tangles are present in this mouse model. For this reason we investigated ( S )-[ 18 F]THK5117 off-target binding to Aβ plaques and MAO-B enzyme in APP/PS1-21 transgenic (TG) mouse model of Aβ deposition. APP/PS1-21 TG and wild-type (WT) control mice in four different age groups (2–26 months) were imaged antemortem by positron emission tomography with ( S )-[ 18 F]THK5117, and then brain autoradiography. Additional animals were used for immunohistochemical staining and MAO-B enzyme blocking study with deprenyl pre-treatment. Regional standardized uptake value ratios for the cerebellum revealed a significant temporal increase in ( S )-[ 18 F]THK5117 uptake in aged TG, but not WT, brain. Immunohistochemical staining revealed a similar increase in Aβ plaques but not endogenous hyper-phosphorylated tau or MAO-B enzyme, and ex vivo autography showed that uptake of ( S )-[ 18 F]THK5117 co-localized with the amyloid pathology. Deprenyl hydrochloride pre-treatment reduced the binding of ( S )-[ 18 F]THK5117 in the neocortex, hippocampus, and thalamus. This study's findings suggest that increased ( S )-[ 18 F]THK5117 binding in aging APP/PS1-21 TG mice is mainly due to increasing Aβ deposition, and to a lesser extent binding to MAO-B enzyme, but not hyper-phosphorylated tau. Highlights: This study investigated ( S )-[ 18 F]THK5117 in vivo binding selectivity and pharmacokinetic properties in APP/PS1-21 mouse model. No NFTs are present in APP/PS1-21 mouse brain, only some endogenous p-tau within the vicinity of Aβ plaques. A clear temporal increase in ( S )-[ 18 F]THK5117 uptake was present in the brain of APP/PS1-21 mouse as they aged. ( S )-[ 18 F]THK5117 binding in APP/PS1-21 mice is mainly due to increasing Aβ plaques, and to a lesser extent due to binding to MAO-B enzyme, but not p-tau.